2018
DOI: 10.1029/2018tc004967
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Deformation of South Korea After the Tohoku‐Oki Earthquake: Deformation Heterogeneity and Seismic Activity

Abstract: Although the 2011 Tohoku-Oki earthquake (Mw 9.0, 11 March 2011) occurred more than 1,000 km from South Korea, it significantly changed the magnitudes and orientations of Global Positioning System (GPS) velocity vectors in the country, which took two years to return to preearthquake values. Then, areas with relatively thick crust show contractional surface deformation, whereas areas with thinner crust show dilatation, suggesting that the deformation pattern is long-term. Although there is no one-to-one correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In year 2013, the average magnitude of velocity in South Korea is observed about 31.332 mm/year. This finding is also found by Kim et al [27] which stated the average magnitude decreased to 31 mm/year after the mainshock of the Tohoku earthquake to 2013. Direction of movement from all stations indicate the direction of movement from Eurasian plate.…”
Section: Figure 12 Velocity Of Continuous Gps Sites In Itrf2008 Referencesupporting
confidence: 86%
“…In year 2013, the average magnitude of velocity in South Korea is observed about 31.332 mm/year. This finding is also found by Kim et al [27] which stated the average magnitude decreased to 31 mm/year after the mainshock of the Tohoku earthquake to 2013. Direction of movement from all stations indicate the direction of movement from Eurasian plate.…”
Section: Figure 12 Velocity Of Continuous Gps Sites In Itrf2008 Referencesupporting
confidence: 86%
“…However, deep earthquakes (depths > 15 km) are poorly observed in the SeKP region, although GPS data reported by ref. 50 shows higher shear strain rates occurring in the area. Therefore, we propose high strain localized shearing through the lower crust and lithospheric mantle.…”
Section: Resultsmentioning
confidence: 92%
“…Some studies suggested that the earthquake-induced significant effects lasted for 2~2.5 years after the 2011 mainshock [ 7 , 9 , 20 ]. However, Blewitt and Lavallée [ 23 ] recommended that a minimum time span of 2.5 years be adopted for velocity solutions intended for tectonic interpretation or reference frame production.…”
Section: Methodsmentioning
confidence: 99%
“…Kim et al [ 20 ] suggested that the 2011 Tohoku-Oki earthquake effects on the Korean Peninsula crustal deformation lasted for approximately two years. However, they analyzed it based on changes in the average velocity with an interval of two years for only about six years after the mainshock.…”
Section: Introductionmentioning
confidence: 99%